2023
DOI: 10.18087/cardio.2023.1.n2118
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between left atrial functions and ambulatory blood pressure variability in patients with heart failure and preserved ejection fraction

Abstract: Aim    The aim of this study was to investigate the relationship between left atrial (LA) abnormalities and ambulatory blood pressure variability (BPV) in heart failure with preserved ejection fraction (HFpEF) patients.Material and methods    In this single-center, prospective study, we included 187 patients with HFpEF. Eighteen patients with poor image quality were excluded from the study. BPV was evaluated using 24-h ambulatory blood pressure (BP) monitoring. The standard deviation of systolic BP (SBP-SD) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recently, more and more attention has been given to the holistic assessment of LA function. Moreover, left atrial structural and functional parameters are evaluated in many cardiac settings other than AF and stroke (Murat et al, 2023 ). Left atrial reservoir strain, when added to the CHA 2 DS 2 ‐VASc variables, has been shown to improve stroke prediction in people without prior AF or stroke (Maheshwari et al, 2023 ).…”
mentioning
confidence: 99%
“…Recently, more and more attention has been given to the holistic assessment of LA function. Moreover, left atrial structural and functional parameters are evaluated in many cardiac settings other than AF and stroke (Murat et al, 2023 ). Left atrial reservoir strain, when added to the CHA 2 DS 2 ‐VASc variables, has been shown to improve stroke prediction in people without prior AF or stroke (Maheshwari et al, 2023 ).…”
mentioning
confidence: 99%